Discourse Framing of Nigeria’s Developmental Issues and Government’s Interventionist Policies in Selected Televised National Addresses of President Muhammadu Buhari (2015 -2021) - Orungbeja, Babatunde Omowaiye; Ajilore, Kolade (European Scientific Journal, ESJ, 2022)
Public addresses constitute potent platforms through which public figures review their policies and articulate their plans. They provide insights to the priorities of the government, elicit public sympathy and support for the government. Contrarily, there has been a seeming dissonance between the national addresses of President Muhammadu Buhari and the reality of the Nigerian citizenry. To this effect, this research purposed to conduct a critical discourse analysis of President Buhari’s national addresses against the backdrop of development in Nigeria between 2015 and 2021. The research explicated the interplay between the concepts of language and ideology in text, for the enactment of human development. The general population of this research comprised all the 27 televised speeches delivered by President Muhammadu Buhari in Nigeria from 2015-2021. The targeted population of 20 national addresses were adopted using a purposive sampling technique. The addresses are the Inaugural Day address of 2015, all New Year’s Day addresses, Democracy Day addresses and all Independence Day addresses. Coding sheet was used to gather data directly from the original full text discourses of the President, as presented to the citizenry. The research findings show that the President’s discourses framed national development issues as direct and key responsibilities of the government which require strategic, sincere and effective interventionist policies. They also revealed nine recurrent themes in the President’s discourses to depict the President’s intense focus on national development in tandem with his pre-election campaign slogan of Security, Economy and Anti-corruption (SEA). The research uncovered linguistic frames comprising pragmatic speech acts of locution, illocution and perlocution in the President’s discourses, to highly and frequently reiterate his ideologies in ensuring national growth and development. The findings also revealed that the President’s discourses framed and propagated ideologies, dissimilar to his military antecedents, for the advancement of his national development interventionist policies. The research concluded that the interplay among President Muhammadu Buhari’s ideology and human development policies in the text of his national addresses between 2015 and 2021, consciously construed his administration’s interventionist policies for the enactment of socio political development against the excruciating challenges in the Nigerian nation. Thus, this research recommended that political leaders should ensure that subsisting problems and those envisaged as the foundation of social order in their societies; the value systems appropriate for social justice, wealth creation and distribution, social efficiency with moral sensitivity and concern for the common good, as deduced from the knowledge of shared values with their citizenry, are pragmatically tackled not only in the discourses, but as well experientially. This research also recommended that politicians and their speech writers should effectively and positively adopt the use of discourse framing to promote societal progressive growth.